Answer:
We conclude that:
∠A = ∠ FEC
Step-by-step explanation:
Given
△ABD ≅ △EFC
To determine:
∠A =
As
△ABD ≅ △EFC
So the triangles △ABD and △EFC are congruent to each other.
- We know that congruent triangles have equal corresponding parts.
Please check the attached graph.
From the graph, it is clear that ∠A is correspondent to ∠E.
∠A = ∠E
From the attached figure, it is clear that:
∠F can also be denoted by ∠ FEC
as
∠A = ∠E
so
∠A = ∠ FEC
Therefore, we conclude that:
∠A = ∠ FEC
Answer:
7⅓
Step-by-step explanation:
2 ÷ 3⁄11 → 2 × 3⅔ >> 7⅓
Dividing by a fraction is the exact same as multiplying by its multiplicative inverse.
* 3⅔ = 11⁄3
* 7⅓ = 22⁄3
I am joyous to assist you anytime.
•••••
•••••
•••••
I'm not for sure if this is what you meant though sorry
Answer:
its -2x
Step-by-step explanation: